Adolescent Psychological Pressure Trends in the Pandemic Covid 19 - Evi Winingsih; Imam Hambali; Fitri Wahyuni (Jurnal Ilmu Keperawatan Jiwa, 2021)
During the Covid 19 pandemic, there were some drastic changes. Social and educational change. This study aims to identify the psychological condition of adolescents. The instrument used was the DASS (Depression Anxiety and Stress Scale). The population in this study were adolescents aged 12 to 21 years from secondary school to undergraduate levels. The sampling technique used in this study was stratified sampling. Data is analyzed using descriptive statistics The results of data analysis showed that of all respondents, the worst psychological condition was sensitivity. As many as 63.2 percent of respondents experienced disorders ranging from mild, moderate, severe to very severe. Meanwhile, the psychological conditions of stress and depression were in the category that was not worrying, namely 35.1 percent of respondents who experienced depression and stress which ranged from mild, moderate, severe and very severe categories. Meanwhile, 74.1 percent was categorized as normal.